2021
DOI: 10.1007/s13203-021-00274-y
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroaromatization of methane over noble metal loaded Mo/H-ZSM-5 zeolite catalysts

Abstract: Dehydroaromatization of methane (MDA) reaction was investigated over platinum modified Mo/H-ZSM-5 catalysts which were pre-carbided at 750 °C. The influence of platinum on the catalytic performance and product selectivity of Mo/H-ZSM-5 catalysts for the MDA reaction at 700 °C were studied. The presence of platinum led to a slight decrease in methane conversion from 7.5 to 4.2%. Aromatic selectivities above 90% were obtained with catalysts containing low platinum loadings (0.5 and 1.0 wt.%), with benzene being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…In the current review we summarize the best results obtained with different catalysts reported during the last 25 years: methane conversion, C 2 products, and benzene yields, as well as the operating conditions (Figure and Table ). ,, ,,, As can be seen from Table , the Mo/HZSM-5 is the most investigated catalyst for the MDA reaction since the very first report in 1993 . Usually, the MDA reaction is carried out at temperatures from 650 to 800 °C, leading to an average benzene selectivity of 70%. ,, Other catalysts for the MDA with lower performance including Fe/HZSM-5, GaN/SBA-15, TaH/SiO 2 , and bimetallic Pt-X/HZSM-5 have been reported.…”
Section: Methane Dehydroaromatization (Mda)mentioning
confidence: 99%
See 4 more Smart Citations
“…In the current review we summarize the best results obtained with different catalysts reported during the last 25 years: methane conversion, C 2 products, and benzene yields, as well as the operating conditions (Figure and Table ). ,, ,,, As can be seen from Table , the Mo/HZSM-5 is the most investigated catalyst for the MDA reaction since the very first report in 1993 . Usually, the MDA reaction is carried out at temperatures from 650 to 800 °C, leading to an average benzene selectivity of 70%. ,, Other catalysts for the MDA with lower performance including Fe/HZSM-5, GaN/SBA-15, TaH/SiO 2 , and bimetallic Pt-X/HZSM-5 have been reported.…”
Section: Methane Dehydroaromatization (Mda)mentioning
confidence: 99%
“…The introduction of several metals promoters to tune the performance of the Mo/HZSM-5 catalysts has been reported; in particular, the nature, concentration of mono- or bi-metallic promoters. The total benzene yield on bimetallic Mo-X/HZSM-5 catalysts and the first order deactivation rate constant of benzene formation are summarized in Table . , ,,,, The bimetallic Mo-X/HZSM-5 based catalysts contain palladium, ruthenium, iridium, zinc, copper, chromium, tungsten, platinum, iron, cobalt, nickel, rhenium, or gallium (Table ). In most of the studies, mono- and bimetallic catalysts with an increase of the total metallic content were compared.…”
Section: Methane Dehydroaromatization (Mda)mentioning
confidence: 99%
See 3 more Smart Citations